An optimal model of agricultural real estate transactions in the light of Professor Aleksander Lichorowicz’s research - Blajer, Paweł (Przegląd Prawa Rolnego, 2024)
The events celebrating the scholarly output of Professor Aleksander Lichorowicz provide a unique opportunity to recall the Jubilarian’s views on the issue of the proper shaping of the principles of the trade in agricultural real estate in Poland. The aim of the article is, on the one hand, to present the most important postulates formulated by Professor Lichorowicz concerning the optimal model of agricultural real estate trade and, on the other hand, to determine the basic directions of legal changes which would make the current Polish model of agricultural real estate trade more rational, consistent with Professor Lichorowicz’s postulates. The article analyses the most important instruments serving the proper shaping of the agricultural system, i.e. instruments protecting agricultural holdings against irrational divisions, instruments preventing excessive concentration of agricultural real estate, the requirement of agricultural qualifications, the pre-emption right to agricultural real estate, instruments related to agricultural lease and inheritance of agricultural holdings. In conclusion, the author expresses an opinion that the Polish legislator, while working on the necessary modification of the principles of agricultural real estate turnover, should extensively draw on the achievements and results of the research conducted by Professor Aleksander Lichorowicz.